2012
DOI: 10.1186/1742-2094-9-196
|View full text |Cite
|
Sign up to set email alerts
|

Primary phagocytosis of viable neurons by microglia activated with LPS or Aβ is dependent on calreticulin/LRP phagocytic signalling

Abstract: BackgroundMicroglia are resident brain macrophages that can phagocytose dead, dying or viable neurons, which may be beneficial or detrimental in inflammatory, ischaemic and neurodegenerative brain pathologies. Cell death caused by phagocytosis of an otherwise viable cell is called ‘primary phagocytosis’ or ‘phagoptosis’. Calreticulin (CRT) exposure on the surface of cancer cells can promote their phagocytosis via LRP (low-density lipoprotein receptor-related protein) on macrophages, but it is not known whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
138
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(143 citation statements)
references
References 35 publications
5
138
0
Order By: Relevance
“…Calreticulin exposure on neurons can act as another 'eat-me' signal, which induces phagocytosis through the low-density lipoprotein receptorrelated proteins (LRPs) on microglia (Fricker et al, 2012b). UDP release from stressed neurons can act as a final engulfment signal by activating P2Y 6 receptors on microglia (Koizumi et al, 2007;Neher et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calreticulin exposure on neurons can act as another 'eat-me' signal, which induces phagocytosis through the low-density lipoprotein receptorrelated proteins (LRPs) on microglia (Fricker et al, 2012b). UDP release from stressed neurons can act as a final engulfment signal by activating P2Y 6 receptors on microglia (Koizumi et al, 2007;Neher et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…PC12 cells are a rat pheochromocytoma cell line that can be differentiated into cells of a neuronal phenotype (Greene and Tischler, 1976). Apoptotic PC12 cells can be phagocytosed by BV-2 cells; this process can require LRPmediated recognition of exposed calreticulin (Fricker et al, 2012b) and/or extracellular annexin A1 binding both PtdSer on PC12 cells and formyl peptide receptor 2 on the BV-2 cells (McArthur et al, 2010). Moreover, BV-2 cells have been suggested to phagocytose 'live' PC12 cells when activated with LPS (McArthur et al, 2010) or PMA , although it was not tested whether the PC12 were in fact alive when phagocytosed, or whether blocking phagocytosis prevented cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Microglia also express Siglec-E, and Siglec-E binds not only to α2,3-and α2,8-sialylated glycans but also to 6SLeC (Redelinghuys et al, 2011). Several studies have identified calreticulin on the cell surface of target cells where it acts as an 'eat-me' signal to induce phagocytosis of these cells (Arosa et al, 1999;Fricker et al, 2012;Raghavan et al, 2013;White et al, 1995). Thus, calreticulin may also play a role as an eat-me signal to induce the removal of synapses.…”
Section: Discussionmentioning
confidence: 99%
“…LPS activation renders microglia ameboid, induces several pro-and anti-inflammatory signaling molecules (Lim et al, 2015; and neurotoxic substances through binding to the CD14/MD-2/Toll-like receptor 4-complex (Fricker et al, 2012;Tokes et al, 2011), and gives rise, among others, to cell spreading by interfering with the organization of the actin cytoskeleton through the alteration of integrin clustering .…”
Section: Or Inmentioning
confidence: 99%
“…Selected CaM inhibitors such as CALMID and TFP, previously reported to have different modes of action (Matsushima et al, 2000;, were quantitatively tested for their ability to modify the microglial morphology, lamellipodia, filopodia and podosome formation, and specific functions such as cell proliferation and survival, protein expression and phagocytosis in unchallenged (control) and lipopolysaccharide (LPS)-challenged cells. Stimulation with LPS was used to evaluate the ability of microglial cells to respond to activation (Fricker et al, 2012;Tokes et al, 2011). …”
Section: Introductionmentioning
confidence: 99%